Hemipotassium hemirubidium digallium(III) manganese(II) tris(phosphate) dihydrate - Zhang, Jing (International Union of Crystallography, 2011)
The title manganese(II) substituted gallophosphate, K(0.5)Rb(0.5)[Ga(2)Mn(PO(4))(3)(H(2)O)(2)], features a three-dimensional network built of PO(4) tetrahedra, GaO(5) trigonal bipyramids and MnO(6) octahedra. The Rb(I) and K(I) ions, which are disordered with respect to each other in a 1:1 ratio, occupy sites within the channels of the framework. The Rb(I)/K(I) and Mn(II) atoms occupy positions of 2 symmetry, as does one of the two P atoms. The Rb(I)/K(I) site is surrounded by six O atoms [2.996 (2)–3.178 (4) Å] in an irregularly-shaped coordination environment. O—H⋯O hydrogen bonds between the water molecules and phosphate O atoms consolidate the crystal packing.